Leveraging donor funds: the switch to commercial funding - Biekpe, Nicholas; Kiweu, Josephat M. (Emerald Group Publishing Limited, 2003)
Purpose – The purpose of this paper is to highlight important factors that influence funding decisions from the perspective of commercial lenders, and suggest commercialization of microfinance as a source of alternative development finance. Design/methodology/approach – A survey of industry experts on funding decisions representative of proponents of commercial microfinance is conducted to help provide views on the most important considerations in their lending practice. Findings – The study finds that specific critical success factors define minimum pre-conditions for microfinance institutions considering commercial funding as an alternative source of finance. The study reveals that the three most important considerations for lending evaluation are transparency in financial reporting, sound financial management, and previous history of borrowing. Research limitations/implications – The study carried out is based on a relatively small sample and puts significant reliance on respondents’ opinions. Originality/value – This is probably one of few attempts to explore the possibility of a linkage between microfinance and capital markets. The paper will be of interest to microfinance institutions, commercial banks, international donors and wholesale funds with an interest in investing in the microfinance industry
Keywords: Critical success factors; Financial institutions; Capital markets; Financing; Gearing